2011
DOI: 10.1073/pnas.1101338108
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of sleep behavior and of its impact on the cross-talk between the brain and peripheral metabolism

Abstract: Rates of obesity have been steadily increasing, along with disorders commonly associated with obesity, such as cardiovascular disease and type II diabetes. Simultaneously, average sleep times have progressively decreased. Recently, evidence from both laboratory and epidemiologic studies has suggested that insufficient sleep may stimulate overeating and thus play a role in the current epidemic of obesity and diabetes. In the human sleep laboratory it is now possible to carefully control sleep behavior and study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 74 publications
1
63
0
1
Order By: Relevance
“…Moreover, short sleep times were also associated with lower leptin and higher ghrelin, hormonal changes that are expected to increase appetite (Taheri et al 2004). The idea that sleep disturbances are associated with aberrant glucose metabolism, hyperglycemia, and insulin resistance, in summary with an increased risk for diabetes, has since been supported by several other studies (Hanlon and Van Cauter 2011;Reutrakul and Van Cauter 2014).…”
Section: Systemic Effects Of Sleep Lossmentioning
confidence: 60%
“…Moreover, short sleep times were also associated with lower leptin and higher ghrelin, hormonal changes that are expected to increase appetite (Taheri et al 2004). The idea that sleep disturbances are associated with aberrant glucose metabolism, hyperglycemia, and insulin resistance, in summary with an increased risk for diabetes, has since been supported by several other studies (Hanlon and Van Cauter 2011;Reutrakul and Van Cauter 2014).…”
Section: Systemic Effects Of Sleep Lossmentioning
confidence: 60%
“…Multiple epidemiological studies have shown that self-reported short sleep duration (defined in most studies as ≤6 h) is associated with negative health outcomes, such as all-cause mortality (2), obesity (3), diabetes (4), cardiovascular disease (5), and impaired vigilance and cognition (6). Laboratory studies, in which the sleep of healthy volunteers was restricted, typically to 4 h for 2-6 d, have identified physiological and endocrine variables that may mediate some of these effects (7), but in general the mechanisms by which insufficient sleep leads to negative health outcomes remain unidentified.…”
mentioning
confidence: 99%
“…Perhaps, birth weight reflects, in part, maternal circadian disruption which leads to her elevated weight. This might occur from a perturbation of metabolism from the circadian disruption (21) which could also manifest as short and disrupted sleep (25).…”
Section: Circadian Gene Expression and Actionmentioning
confidence: 99%